فاعلية استراتيجيتي "الأمثلة المحلولة - حل المشكلات" ببيئة تعلم إلكترونية في تنمية مهارات إنتاج المشروعات البرمجية لدى طلاب شعبة إعداد معلم الحاسب الآلي - مصطفى، يحى إبراهيم محمد; هنداوي، أسامة سعيد علي; بكير، سماح زغلول حسن (جامعة الزقازيق - كلية التربية النوعية, 2022)
هدف البحث تحديد فاعلية استراتيجيتي التعلم (الأمثلة المحلولة مقابل حل المشكلات) ببيئة تعلم إلكترونية في تحصيل طلاب وطالبات الفرقة الثانية -شعبة إعداد معلم الحاسب الآلي كلية التربية النوعية جامعة الزقازيق وأدائهم لمهارات إنتاج المشروعات البرمجية، وقد تم إجراء التجربة على عينة عشوائية مكونة من (60) طالبا وطالبة من طلاب الفرقة الثانية، وقسمت العينة العشوائية إلى مجموعتين تجريبيتين (مجموعة (1) درست المحتوى التعليمي باستراتيجية الأمثلة المحلولة -مجموعة (2) درست المحتوى التعليمي باستراتيجية حل المشكلات)، واستخدم البحث أداتين بحثيتين؛ هما: (اختبار التحصيل المعرفي المرتبط بالمهارات -بطاقة ملاحظة أداء تلك المهارات)، وبعد تطبيق أدوات البحث قبليا وبعديا وتطبيق البرنامج على أفراد العينة تم التوصل إلى النتائج التي أشارت إلى وجود فرق دال إحصائيا بين متوسطي درجات طلاب العينة ككل في القياس القبلي والقياس البعدي لاختبار التحصيل المعرفي، وبطاقة ملاحظة أداء المهارات لصالح القياس البعدي، مما يؤكد فاعلية بيئة التعلم الإلكترونية في زيادة التحصيل المعرفي وأداء المهارات، كذلك أشارت نتائج البحث إلى وجود فرق دال إحصائيا بين متوسطي درجات المجموعة التي درست المحتوى باستراتيجية الأمثلة المحلولة، ودرجات المجموعة التي درست المحتوى باستراتيجية حل المشكلات على التحصيل المعرفي والأداء العملي للمهارات لصالح مجموعة استراتيجية الأمثلة المحلولة، وتؤكد هذه النتيجة أهمية استخدام استراتيجية الأملة المحلولة في تنمية التحصيل المعرفي والأداء العملي للمهارات. The aim of the research is to determine the effectiveness of the two learning strategies (Worked examples/ problem solving) in an e-learning environment in the achievement of male and female students of the second year Computer Teacher Preparation Division, Faculty of Specific Education, Zagazig University, and their performance of the skills of producing programming projects. The experiment was conducted on a random sample consisting of (60) male and female students of the second year, and the random sample was divided into two experimental groups (group (1) studied the educational content using the worked examples strategy- group (2) studied the educational content using the problem-solving strategy). The research used two research tools; They are: (Cognitive achievement test related to skills- observation card for the performance of those skills, After pre and post application of the research tools, and application of the program to the sample members, the results of the research indicated that there was a statistically significant difference between the mean scores of the sample students as a whole in the pre- and post-measurement of the cognitive achievement test, and the skills performance observation card in favor of the post-measurement, which confirms the effectiveness of the e-learning environment in increasing cognitive achievement and skills performance, The results of the research also indicated that there was a statistically significant difference between the mean scores of the group that studied the content with the worked examples strategy, and the scores of the group that studied the content with the problem-solving strategy on the cognitive achievement and practical performance of skills in favor of the group of the worked examples strategy. This result confirmed the importance of using the worked examples strategy in the development of cognitive achievement and practical performance of skills.
Keywords: الاستراتيجيات التعليمية -- التعليم الإلكتروني -- المهارات الرقمية -- طلبة الجامعات